Influence of artificial landmarks on the accuracy of complete arch scans in the partially edentulous maxilla: an in vitro study - Waldecker, Moritz; Bömicke, Wolfgang; Awounvo Awounvo, Junior Sinclair; Rammelsberg, Peter; Rues, Stefan (The journal of prosthetic dentistry, 2024)
Statement of problem - Scan path length and the presence of edentulous alveolar ridge sections have a negative influence on scanning accuracy. How different artificial landmarks combined with an adapted scanning method affect accuracy is unclear. - Purpose - The purpose of this in vitro study was to determine the influence of 2 different artificial landmarks combined with an adapted scanning method on the scanning accuracy of a partially edentulous maxillary model. - Material and methods - The model simulated a maxilla with 6 prepared teeth to accommodate a complete arch fixed partial denture. Five ceramic precision balls (ball center P1-P5), distributed buccally to the dental arch, were used to detect the dimensional and angular changes between the reference model and the intraoral scans. One intraoral scanner (Primescan) was used to make 30 scans each with either the scanning strategy recommended by the manufacturer (M) or with an adapted scanning strategy and the use of a bar (B) or 4 plates (P) as artificial landmarks in the dorsal palate. Data were statistically analyzed using a generalized least squares regression model (α=.05). - Results - Scanning with artificial landmarks reduced the maximum absolute distance deviations (M: 249 μm, B: 190 μm, P: 238 μm) and the maximum angle deviations (M: 0.31 degrees, B: 0.28 degrees, P: 0.26 degrees). Vertical distance deviations were improved by 10 to 50% with the use of artificial landmarks. Absolute mean distance deviations were significantly lower for group M (P<.001). In contrast, with artificial landmarks, mean angle (P<.001) and mean vertical distance deviations (P<.014) improved significantly. - Conclusions - Scanning with artificial landmarks in the dorsal palate combined with an adapted scanning method improved the scanning accuracy and reliability of vertical distance deviations.
Gesehen am 25.03.2025